2009
DOI: 10.1177/0021998309353214
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Steady State Creep in Functionally Graded Thick Cylinder Subjected to Internal Pressure

Abstract: The steady state creep behavior in an isotropic functionally graded composite cylinder, subjected to internal pressure has been investigated. The cylinder is assumed to be made of composite containing silicon carbide particles in a matrix of pure aluminum. The creep behavior of the material has been described by threshold stress based creep law with a stress exponent of five. The effect of imposing linear particle gradient on the distribution of stress and strain rates in the composite cylinder has been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The magnitude of strain observed in non-linear FGM cylinders (C3) is the lowest over the entire radius when compared to linear FGM cylinder (C2) and uniform composite cylinder C1. The superiority of creep response of FGM cylinder over non-FGM cylinder, as indicated in the present study, is also confirmed by earlier reported work of Singh and Gupta (2010) for linear FGM cylinder made of Al-SiC p .…”
Section: Fe Modeling Of Creepsupporting
confidence: 92%
See 2 more Smart Citations
“…The magnitude of strain observed in non-linear FGM cylinders (C3) is the lowest over the entire radius when compared to linear FGM cylinder (C2) and uniform composite cylinder C1. The superiority of creep response of FGM cylinder over non-FGM cylinder, as indicated in the present study, is also confirmed by earlier reported work of Singh and Gupta (2010) for linear FGM cylinder made of Al-SiC p .…”
Section: Fe Modeling Of Creepsupporting
confidence: 92%
“…It is important to mention that similar to work of Singh and Gupta (2010) for linear FGM cylinder made of Al-SiC p , the present analysis could not be carried out for cylinder made of Al-SiC p . It is attributed to the fact that the value of creep parameter B 96 MMMS 10,1 for Al-SiC p composite is less than 10 À29 (Singh and Ray, 2001), which is below the recommended minimum of 10 À27 (refer Section 11.2.4 of ABAQUS, 2004).…”
Section: Distribution Of Reinforcementmentioning
confidence: 98%
See 1 more Smart Citation
“…P Al is pure aluminum property, P SiC is pure silicon carbide property, and V (r ) is volume content of silicon carbide particles at radius r . We need to point out that this kind of rule of mixtures is not appropriate for every kind of property; however, for Al-SiC composite, several investigators [3,7,11] have used this kind of radial-dependent property for some of mechanical and thermal properties. Based on Eq.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Rearchers have used various mathematical methods such as Runge Kutta 4th order, finite difference method (FDM), shooting method, complementary function method (CFM), homotopy analysis method for obtaining the solution of steady state creep in disks and cylinders made up of functionally graded materials. Creep models based on iterative technique, finite element method (FEM) and Seth’s transition theory for obtaining stress distribution in functionally graded rotating disks and cylinders can be also found in the literature [ 23 , 24 , 25 ]. Nie and Batra [ 26 ] studied the problem of material tailoring to obtain desired stress field in hollow cylinder made up of functionally graded in-compressible material with radially varying shear modulus.…”
Section: Introductionmentioning
confidence: 99%